Decreased expression of the immediate early protein, ICP4, by deletion of the tegument protein VP22 of equine herpesvirus type 1 - OKADA, Ayaka (J Vet Med Sci, 2017)
VP22 is a major tegument protein of equine herpesvirus type 1 (EHV-1). In the present study, we examined functions of VP22 in EHV-1 replication by viral protein expression analyses in cells infected with the VP22-deficient virus. The expressions of several viral proteins in the cells infected with the VP22-deficient virus were lower than those in the cells infected with the parent virus. One of the weakly expressed proteins was identified as ICP4, which is a major regulatory protein encoded by an immediate early gene of EHV-1. A real-time PCR analysis showed that the mRNA expression of ICP4 was the same in cells infected with the parent and VP22-deficient viruses. Hence, VP22 appears to promote synthesis of ICP4 post-transcriptionally.